2022
DOI: 10.1021/acs.jpcc.2c04266
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Ruthenium Films Using Ruthenium Diketonates and O2, H2, or N2O: The Role of Ruthenium Etching

Abstract: The evolution of the surface during the steps that comprise the atomic layer deposition (ALD) of ruthenium films on a nickel substrate using tris­(2,2,6,6-tetramethyl-3,5-heptanedionato)­ruthenium­(III) (Ru­(tmhd)3) and molecular oxygen was characterized using a combination of X-ray photoelectron (XPS) and reflection–absorption infrared (RAIRS) spectroscopies. The uptake of the Ru metalorganic precursor was determined to be activated, involving the average loss of two out of the three ligands (and the retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…We have recently advanced the idea of using nitrous oxide as a source of O• radicals: N 2 O is in some ways similar to O 3 , but it is more stable, and upon dissociation yields N 2 , an inert gas, as the byproduct. We have shown that, indeed, Ru metal films (using Ru(tmhd) 3 ) are difficult to grow with O 2 but can be developed using N 2 O (figure 10, right panel) [93]. However, when attempting to deposit Mn on a silicon dioxide substrate using MeCpMn(CO) 3 and N 2 O, a multicomponent film was found to form instead comprising of manganese silicate and manganese silicide phases [171].…”
Section: Selection and Role Of Co-reactantmentioning
confidence: 94%
See 2 more Smart Citations
“…We have recently advanced the idea of using nitrous oxide as a source of O• radicals: N 2 O is in some ways similar to O 3 , but it is more stable, and upon dissociation yields N 2 , an inert gas, as the byproduct. We have shown that, indeed, Ru metal films (using Ru(tmhd) 3 ) are difficult to grow with O 2 but can be developed using N 2 O (figure 10, right panel) [93]. However, when attempting to deposit Mn on a silicon dioxide substrate using MeCpMn(CO) 3 and N 2 O, a multicomponent film was found to form instead comprising of manganese silicate and manganese silicide phases [171].…”
Section: Selection and Role Of Co-reactantmentioning
confidence: 94%
“…The ALD reactor, shown in the left side of figure 2, is also kept under vacuum but can be pressurized to carry out the ALD steps; it includes a setup for RAIRS that can be used in situ during gas exposures. The sample is mounted on a transferring rod for fast exchange between these two chambers without exposure to the outside atmosphere, and also to cool down and/or resistively heat it to any temperature between 150 and 1100 K. We have used this type of equipment extensively already, for studies of both catalytic [89][90][91] and ALD [92][93][94] systems. Instruments designed with a similar philosophy have been recently reported by other research groups [95][96][97].…”
Section: Mechanistic Studies Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation